Dukungan sosial dan kecemasan berkendara pada penyintas kecelakaan lalu lintas - Daniel Christanto; IGAA Noviekayati (INNER: Journal of Psychological Research, 2022)
The aims of this study was to determine the relationship between social support and driving anxiety in traffic accident survivors and differences in driving anxiety in terms of gender, age, employment status, accident rate, and the time the accident was experienced. The research design uses correlational and comparative quantitative research. This study was conducted on 73 participants with an age range of 16-30 years who had experienced an accident. The research instrument was developed by the researcher based on the concept of social support by Weiss and driving anxiety by Zinzow & Jeffirs. This study used the Spearman’s Rho test, the Mann-Whitney test, and the Kruskal-Wallis test. The results showed a negative correlation between social support and driving anxiety. There are differences in driving anxiety based on gender, age, and time of the accident. This shows that the higher the social support, the lower the anxiety of driving and vice versa, the anxiety of driving is more prone to be experienced by women, who are younger, and have just had an accident. Keywords: Age; Driving Anxiety; Gender; Road Traffic Accident; Social Support.